AND THE ISSUE OF VIOLENCE AGAINST WOMEN AND GIRLS IN PRESS OF UZBEKISTAN AND ITS INTERNET-SITES (Scientific journal of the Fergana State University, 2023)
The article deals with the problem of domestic violence against women, which is currently topical and relevant throughout the world and presents an analysis of the work on preventing of this phenomenon. In addition, the measures taken for protection of women from various domestic violence in the family have been thoroughly discussed.